Relationship between office competencies and job satisfaction among administrative support personnel - Aminu Ibrahim, Batagarawa; Lope Pihie, Zaidatol Akmaliah (Impact Journals, 2014)
The purpose of this paper is to examine the relationship between office competencies and job satisfaction among the Administrative Support Personnel (ASP) in Katsina State tertiary institutions. Office competencies required to operate as ASP in Nigerian context are considered. These needed competencies are the email, internet, word processing, spreadsheet, database, communication and teamwork. Satisfied workers tend to put in their best resulting in the mass production of goods and services. Variables of job satisfaction, according to Herzberg’s motivation/hygiene theory are the motivators called satisfiers which include responsibility, advancement, achievement, recognition, and the work itself. The hygiene factors he referred to as dissatisfies are the organizational policy, supervision, working conditions, interpersonal relationships, and salary. Based on the literature, the paper concluded that office competencies lead to job satisfaction.